2011
DOI: 10.2169/internalmedicine.50.4398
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial Aspergillosis following Primary Cutaneous Aspergillosis in a Lung-Transplant Recipient

Abstract: Invasive aspergillosis, a major problem during the post-transplant period, typically presents with pneumonia or tracheobronchitis in lung transplant recipients. In contrast, primary cutaneous aspergillosis is very rarely observed in lung-transplant recipients. In this report, we describe a case of tracheobronchial aspergillosis following primary cutaneous aspergillosis in a lung-transplant recipient. Early diagnosis of tracheobronchial aspergillosis is important because occult tracheobronchial aspergillosis ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Brinca et al presented a case report of cutaneous aspergillosis in 2011, in this study they found a pulmonary primary focus of infection (13). Cho et al were also presented a case report of tracheobronchial aspergillosis following primary cutaneous aspergillosis in a lung-transplant recipient (22). Special attention to pulmonary symptoms and/or signs may determine whether an evaluation for pulmonary aspergillosis is needed.…”
Section: Discussionmentioning
confidence: 70%
“…Brinca et al presented a case report of cutaneous aspergillosis in 2011, in this study they found a pulmonary primary focus of infection (13). Cho et al were also presented a case report of tracheobronchial aspergillosis following primary cutaneous aspergillosis in a lung-transplant recipient (22). Special attention to pulmonary symptoms and/or signs may determine whether an evaluation for pulmonary aspergillosis is needed.…”
Section: Discussionmentioning
confidence: 70%
“…8 Another case report of tracheobronchial aspergillosis following primary cutaneous aspergillosis in a lungtransplant recipient was reported. 9 However, we have not found any reported case of primary cutaneous aspergillosis in an immunocompetent patient after searching in PubMed and Google Scholar.…”
Section: Discussionmentioning
confidence: 92%
“…ITBA is a rare form of invasive pulmonary aspergillosis. In previous reports, immunocompromised patients, such as those who had received organ or bone marrow transplantation, those being treated with immunosuppressive agents such as steroids and those suffering from acquired immu- (6,(10)(11)(12). The symptoms are usually non-specific, such as cough, dyspnea and respiratory failure (9,13,14).…”
Section: Discussionmentioning
confidence: 99%